Farm power policies and groundwater markets: contrasting Gujarat with West Bengal (1990–2015) - Shah, Tushaar; Chowdhury, S.D. (2021)
This chapter examines the effects of such power sector reforms on the functioning of groundwater markets at the local level by comparing the cases of Gujarat and West Bengal. In Gujarat, an innovative power sector reform program (called Jotigram Yojona) was launched. The West Bengal state government, on the contrary, introduced a metering system to agriculture in place of the flat tariff while abolishing the electric tube well permit system. Consequently, the groundwater markets shrunk and/or the water charges paid by less resourceful farmers to the well owners increased in both states. The results imply that the power sector reforms, although they contributed to the reduction of the nexus problem, produced severe ill effects upon the farmers placed in weaker market positions.